Development of Quantum Hermite-Hadamard Type Inequalities Using Green’s Function Techniques (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we investigate the quantum Hermite-Hadamard inequality using the Green's function. This process leads to the derivation of novel quantum identities, which are then employed to establish novel inequalities. Utilizing these identities, we establish novel inequalities. The main results of the paper are derived using various techniques such as q-identities, convexity and Jensen inequality. Furthermore, the study provides numerical validation and graphical representations to support the main results.
Keywords: Convex function; HH Inequality; Quantum integrals